The Moral Limits of Markets: A Critique on the Book “What Money Can't Buy?” - Hamid Padash (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Michael Sandel (2012) criticizes the neoliberal policies that were presented and implemented in many countries from 1970s in his book”What Money Can't Buy: The Moral Limits of Markets”. The writer has criticized a situation in which neoliberal policies have led to commodification and monetization of social relations. He shows how our daily and routine experiences have lost their social and collective aspects. The individuals assess and justify their incentives on the material profit (and loss) basis. This paper is structured in the framework of the formal critique and content critique. It is argued, in this paper, that there are important differences between these features which are not equal.   But, the writer categorizes all of them in just one category and presents similar explanation for them. This is the most important critique to the book that describes itself as a book for ”how we live in the market-oriented capitalist world”.